PENYADAPAN GETAH KERUING (Dipterocarpus spp) DI HUTAN DESA DUSUN BENUA KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBU RAYA BERDASARKAN DIAMETER POHON - M. Idham; Sudirman Muin; Iskandar AM (Universitas Tanjungpura, 2013)
Keruing tree (Dipterocarpus spp) produced sap which is used for caulking boats; varnish and paint cure for a particular wound. The research aims to determine the sap production keruing intercepted on several different tree diameter classes. Research carried out in the area of ​​Village Forest at Benua Village Sungai Ambawang Kubu Raya District West Kalimantan Province. Keruing tree is tapped is a type of Keruing Kipas (Dipterocarpus spp) with a diameter of 30-39 cm and a diameter of 40-49 cm. Time of tapping carried out in three times, i.e. morning, noon and evening. Tapping stream forms a V-shaped with a height of 130 cm from the ground with a length of 20 cm, a width of 3 cm with an inclination of 45o flat surface. The results of research show the average amount of sap production of Keruing according to grade level diameter tree is a tree with a diameter of 30-39 cm class produce sap Keruing of 73.1 grams and a tree with a diameter of 40-49 cm class produce sap Keruing of 112.18 grams. The study concluded that the larger the diameter of the Keruing tree will produce the higher sap production. This is due to the greater diameter of the tree, the heartwood of the tree will be greater, and the higher content of Keruing sap contained in the sapwood of trees. Keywords: Dipterocarpus spp, Keruing Kipas, sap, times of tapping, tree diameter